Synthesis route to pyrrolones from -cyano ,-unsaturated ketones and -isocyano esters by oxidative dearomatization of 2-aminofuran intermediates - Mahida, Anil K.; Kale, Someshwar B.; Das, Utpal (European Journal of Organic Chemistry, 2017)
An efficient method for the catalyst/promoter-free synthesis of tetrasubstituted furan derivatives proceeding through the [4+1] cycloaddition of isocyanoacetates with electron-deficient olefins was developed. The products were obtained in good to excellent yields without any column chromatography. Oxidative dearomatization of these furans was achieved only in the presence of oxygen, which led to pyrrolones in high yields.

Synthesis of N-functionalized 2,3-disubstituted benzofurans/naphthofurans from para-quinone methides and isocyanides via the [4+1] annulation pathway - Kale, Someshwar B.; Kumar, Manish; Shinde, Dinesh R.; Krishna, Gamidi Rama; Das, Utpal (Organic Chemistry Frontiers, 2023)
A scandium triflate catalyzed [4 + 1] cycloaddition reaction of 2-hydroxy-substituted para-quinone methides and isocyanides has been developed. This operationally simple, efficient and practical protocol provides straightforward access to a variety of N-functionalized 2,3-disubstituted benzofuran/naphthofuran derivatives with broad functional group compatibility and good scalability.

Synthesis of benzannulated [5,6] oxa-fused/spiro-lactones via [4+2] cycloaddition with quinone methides: new insights into deconjugated butenolide reactivity - Kumar, Manish; Kale, Someshwar B.; Jawahar, Subramani; Barkade, Apurva D.; Das, Utpal (Journal of Organic Chemistry, 2025)
In this study, we unfold a Lewis-acid-catalyzed inverse electron demand hetero Diels-Alder (IEDHDA) [4 + 2] reaction, leveraging the unique beta-selective nucleophilicity of deconjugate lactone in conjunction with quinone methides for the synthesis of polycyclic fused and spiro acetals in a one-pot process. This cascade annulation reaction efficiently generates 3/4 chiral centers with high diastereoselectivity. The developed methodology proceeds under mild reaction conditions and exhibits a broad substrate scope for fused and spiro acetal formation.